Perception of Science Teacher Candidates Toward Creative Thinking Ability - Agus Muliadi; Joni Rokhmat; Aliefman Hakim; AA Sukarso (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to explore the perceptions of prospective science teacher students regarding creative thinking abilities. This study is an exploratory research with research subjects as many as 14 biology education students. The research instrument used is a closed questionnaire which has been developed referring to indicators of creative thinking abilities, namely fluency, flexibility, originality and elaboration. The questionnaire has answers using a Likert scale that has been validated by experts and declared valid. This research data was analyzed using quantitative descriptive statistics and inferential statistics with the Anova test. The results of this research are (1) biology education students have an average perception score regarding creative thinking abilities, namely the Fluency indicator is 2.52 in the Tall category, Flexibility is 2.61 in the Tall category, Originality is 2.63 in the Tall category, and Elaboration of 2.67 in the Tall category; (2) there is no significant difference in students' perceptions of creative thinking abilities on the indicators of fluency, flexibility, originality and elaboration, as evidenced by the results of the Anova test with a significance value of 0.719>0.05.